2019
DOI: 10.1371/journal.pone.0219064
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 (PAI-1) expression in endometriosis

Abstract: Purpose Deep infiltrating endometriosis (DIE) is defined as an endometriotic lesion penetrating to a depth of >5 mm and is associated with pelvic pain, but the underlying mechanisms are unclear. Our objective is to investigate whether plasminogen activator inhibitor-1 expression (PAI-1) in endometriotic tissues is increased in women with DIE. Methods In this blinded in vitro study, immunohistochemistry and Histoscore were used to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This system regulates extracellular fibrin proteolysis and influences cell invasion, migration, and ECM remodeling ( Duffy, 2004 ). SERPINE1 is a biomarker for endometriosis, with high levels of expression observed in ovarian and deep infiltrating endometriosis ( Alotaibi et al, 2019 ; Gilabert-Estellés et al, 2003 ; Ramón et al, 2005 ; Ye et al, 2017 ). We examined a published RNA-seq dataset of human endometrial organoids and observed that SERPINE1 was upregulated in organoids derived from ectopic endometrial tissue compared to healthy endometrial tissue (log 2 fold change [FC] = 3.86, FDR = 0.051) ( Boretto et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This system regulates extracellular fibrin proteolysis and influences cell invasion, migration, and ECM remodeling ( Duffy, 2004 ). SERPINE1 is a biomarker for endometriosis, with high levels of expression observed in ovarian and deep infiltrating endometriosis ( Alotaibi et al, 2019 ; Gilabert-Estellés et al, 2003 ; Ramón et al, 2005 ; Ye et al, 2017 ). We examined a published RNA-seq dataset of human endometrial organoids and observed that SERPINE1 was upregulated in organoids derived from ectopic endometrial tissue compared to healthy endometrial tissue (log 2 fold change [FC] = 3.86, FDR = 0.051) ( Boretto et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…LtfCre 0/+ ; (Gt) R26 Pik3ca*H1047R ; Arid1a fl/fl eutopic endometrial epithelia and ectopic lesions showed increased SERPINE1 by IHC, which was not observed in LtfCre 0/+ ; (Gt)R26 Pik3ca*H1047R ; Arid1a fl/fl ; Ep300 fl/fl ( Figures 7G and 7H ). Among a cohort of deep infiltrating and ovarian endometriosis tissue samples ( Alotaibi et al, 2019 ), samples with a loss of ARID1A expression displayed the highest expression of SERPINE1 by IHC ( Figures S6A and S6B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations